Association between serum levels of 12 different cytokines and short-term efficacy of chemoradiotherapy in esophageal squamous cell carcinoma - Yaping Zhang; Qiufeng Qi; Ming Zhu; Yun Peng; Yanqing Bao; Jun Liu; Yanzhi Bi; Min Xiao; Shaohua Chi; Yongping Liu (Discover Oncology)
Abstract Background Esophageal squamous cell carcinoma (ESCC) has a poor prognosis, with chemoradiotherapy (CRT) being a key treatment method. This study focused on circulating cytokines as potential predictors of treatment response and prognosis in patients with ESCC. Materials and methods Serum samples were collected from 36 ESCC patients, and 12 different cytokines were quantified using a multiplex immunofluorescence assay. We used non-parametric Wilcoxon unpaired rank tests to examine the relationship between cytokine concentrations and clinical outcomes. The duration of progression-free survival was assessed through imaging studies and telephone follow-ups. Kaplan–Meier survival plots, analyzed with the log-rank test, were utilized to depict survival trends. Results Pre-treatment serum IL-8 levels were significantly elevated in patients with lymphoid metastases (p = 0.036). Lower initial levels of IL-8 and IL-1β were observed in patients with partial response group compared to those with stable disease (p = 0.002, p = 0.01). Elevated baseline levels of IL-8 and interferon-gamma (IFN-γ) were correlated with a poorer prognosis. Higher levels of IL-5 and IFN-γ levels following therapy were associated with worse outcomes. Conclusions Our findings indicate that IL-8, IL-1β, IL-5, and IFN-γ may serve as potential biomarkers for treatment efficacy and prognosis in ESCC. Patients with low levels of IL-8 and IL-1β demonstrate a favorable response to CRT. Elevated serum levels of IL-8, IL-1β, IFN-γ, and IL-5 may predict poorer clinical outcomes.